Offshore permafrost decay and massive seabed methane escape in water depths >20 m at the South Kara Sea shelf - Portnov, Alexey; Mienert, Jurgen; Cherkashov, Georgy; Rekant, Pavel; Semenov, Peter; Serov, Pavel; Vanshtein, Boris; Smith, Andrew James (Geophysical Research Letters, 2013)
Since the Last Glacial Maximum (~19 ka), coastal inundation from sea-level rise has been thawing thick subsea permafrost across the Arctic. Although subsea permafrost has been mapped on several Arctic continental shelves, permafrost distribution in the South Kara Sea and the extent to which it is acting as an impermeable seal to seabed methane escape remains poorly understood. Here we use >1300 km of high-resolution seismic data to map hydroacoustic anomalies, interpreted to record seabed gas release, on the West Yamal shelf. Gas flares are widespread over an area of at least 7500 km2 in water depths >20 m. We propose that continuous subsea permafrost extends to water depths of ~20 m offshore and creates a seal through which gas cannot migrate. This Arctic shelf region where seafloor gas release is widespread suggests that permafrost has degraded more significantly than previously thought.